Update in minimally invasive periorbital rejuvenation with a focus on platelet‐rich plasma: A narrative review. (17th March 2020) - Kassir, Martin; Kroumpouzos, George; Puja, Priya; Katsambas, Andreas; Galadari, Hassan; Lotti, Torello; Abdelmaksoud, Ayman; Grabbe, Stephan; Juchems, Eva; Goldust, Mohamad
Abstract: Background: The periorbital region is among the first areas to be affected by the process of aging, which is influenced by genetic and constitutional factors. As the region plays an important role in overall facial appearance, rejuvenation of the area has immense cosmetic benefit and various treatment modalities have been used to achieve the same. Aims: This article reviews commonly used non‐surgical and minimally invasive modalities for periorbital rejuvenation. Methods: The literature research considered published journal articles (clinical trials or scientific reviews). Studies were identified by searching electronic databases (MEDLINE and PubMed) and reference lists of respective articles. Only articles available in English were considered for this review. Results: Autologous platelet rich plasma (PRP) is increasingly used in dermatology for skin and hair conditions. The use of PRP is rapidly growing in popularity as a modality to achieve skin rejuvenation. The mechanism by which PRP leads to skin rejuvenation is by increasing the dermal fibroblast proliferation, expression of matrix metalloproteinase and collagen synthesis. Conclusion: The evidence discussed in this article indicates the increasing importance of minimally invasive modalities in periorbital rejuvenation and a promising role for PRP as solo therapy or in multimodality regimens.